Experimental Vibration Analysis for Civil Structures Testing, Sensing, Monitoring, and Control - Conte, Joel P.; Astroza, Rodrigo; Benzoni, Gianmario; Feltrin, Glauco; Loh, Kenneth J.; Moaveni, Babak; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This edited volume presents selected contributions from the International Conference on Experimental Vibration Analysis of Civil Engineering Structures held in San Diego, California in 2017 (EVACES2017). The event brought together engineers, scientists, researchers, and practitioners, providing a forum for discussing and disseminating the latest developments and achievements in all major aspects of dynamic testing for civil engineering structures, including instrumentation, sources of excitation, data analysis, system identification, monitoring and condition assessment, in-situ and laboratory experiments, codes and standards, and vibration mitigation.
Experimental evaluation of the effect of geometric nonlinearities on structural resonances -- Vortex-induced vibration of stay cables, verification on the footbridge -- The selection of a dynamic model of a RC chimney based on in situ research -- A new approach to damage detection in bridges using machine learning -- Vibration based damage identification method for cantilever beam using artificial neural network -- Vertical vibration mitigation of a bridge cable using a non smooth absorber under gravity -- Advanced statistical techniques applied to raw data for structural damage detection -- A new system identification method operated in the pole domain -- Identification of extremely close modes with an improved stochastic subspace algorithm.
Keywords: Civil engineering; Multibody systems; Vibration; Mechanics, Applied; Civil Engineering; Multibody Systems and Mechanical Vibrations